Seismic source in the Iberian-African plate boundary - Buforn, Elisa (2012)
The plate boundary between Iberia and Africa has been studied using data on seismicity and focal mechanisms. The region has been divided into three areas: A; the Gulf of Cadiz; B, the Betics, Alboran Sea and northern Morocco; and C, Algeria. Seismicity shows a complex behavior, large shallow earthquakes (h < 30 km) occur in areas A and C and moderate shocks in area B; intermediate-depth activity (30 < h < 150 km) is located in the depth earthquakes (h » 650 km) are located to the south of Granada. Moment rate, slip velocity and b values have been estimated for shallow shocks, and show similar characteristics for the Gulf of Cadiz and Algeria, and quite different ones for the central region. Focal mechanisms of 80 selected shallow earthquakes (8 ‡ mb ‡ 4) show thrust faulting in the Gulf of Cadiz and Algeria with horizontal NNW-SSE compression, and normal faulting in the Alboran Sea with E-W extension. Focal mechanisms of 26 intermediate-depth earthquakes in the Alboran Sea display vertical motions, with a predominant plane trending E-W. Solutions for very deep shocks correspond to vertical dip-slip along N-S trends. Frohlich diagrams and seismic moment tensors show different behavior in the Gulf of Cadiz, Betic-Alboran Sea and northern Morocco, and northern Algeria for shallow events. The stress pattern of intermediate-depth and very deep earthquakes has different directions: vertical extension in the NW-SE direction for intermediate depth earthquakes, and tension and pressure axes dipping about 45 ° for very deep earthquakes. Regional stress pattern may result from the collision between the African plate and Iberia, with extension and subduction of lithospheric material in the Alboran Sea at intermediate depth. The very deep seismicity may be correlated with older subduction processes.